Proposta para modelo de gerenciamento de risco, visando a mitigação de acidentes ampliados na mineração - Fernando Discacciati Cruz (2021)
Unwanted and devastating events over a high potential for fatality in the aspects of social, environmental, and physical and mental health of the exposed beings, with gravity and dimension overpass the spatial and temporal borders of their source, are referred to as: major accidents. In view of this concept and the recurrence of facts, in the Brazilian mining-metallurgical sphere, questions have surfaced about risk management practices in mining. The scale of the damage and the resonance of the victims' voices raised doubts about the sustainability of mining processes. Is it possible to do responsible and productive mining? What would be the roles and responsibilities of stakeholders? What practices and tools are needed to guarantee sustainable development in mining? Therefore, a study that seeks to rescue the notion of mining major accidents is relevant to answer these questions. At the methodological level, a continuous model of control and management of systems subject to failure was developed, aimed at mining. The frame of the model is on the knowledge state of risk management techniques and analysis of previous accidents. In order to exemplify, a protocol was admitted and tested in two mining operations. The results indicated that it is necessary to increase the application of risk management concepts and techniques to the Brazilian mining sector, and in possession of the understanding and evolution of the topics of the developed model, it is possible to achieve responsible, productive mining and that its damage, if any, can be mitigated.